Self-Fulfillment - Gewirth, Alan (Book collections on Project MUSE., 2001)
Cultures around the world have regarded self-fulfillment as the ultimate goal of human striving and as the fundamental test of the goodness of a human life. The ideal has also been criticized, however, as egotistical or as so value-neutral that it fails to distinguish between, for example, self-fulfilled sinners and self-fulfilled saints. Alan Gewirth presents here a systematic and highly original study of self-fulfillment that seeks to overcome these and other arguments and to justify the high place that the ideal has been accorded. He does so by developing an ethical theory that ultimately g.